Optimizing cadaveric models for endovascular training through effective preparation techniques - Christopher Ibarra, MD; Alex D. Contreras, MS; Samantha Cervantes, MS; Rebecca Barnes, MBS; Stuart J. Corr, PhD; Alan B. Lumsden, MD; Maham Rahimi, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Objective: This study highlights how a thorough preparation process is crucial to achieving successful cadaveric models for endovascular training. By sharing our descriptive report of procedural experiments and detailed preparation techniques, we demonstrate the importance of this process in creating high-fidelity models that enhance training effectiveness. Methods: Two fresh frozen cadavers (FFCs) were prepared for a high-fidelity vascular training model. Frozen at −20 °F, they were transported under refrigerated conditions and thawed over 3 days at 60 to 65 °F. Vascular patency was assessed using robotic C-arm imaging. A motorized pump simulated arterial hemodynamics, whereas manual perfusion enhanced cerebral visualization. Vascular access was established via femoral, carotid, and radial/ulnar arteries under ultrasound guidance. Procedures were performed in a hybrid operating room with advanced imaging. The model’s effectiveness was evaluated through pulmonary thrombectomy in one cadaver and simulated ruptured abdominal aortic aneurysm repair in the other. Results: The cadaveric models demonstrated significant versatility, allowing for the successful replication of both a pulmonary embolism and a ruptured abdominal aortic aneurysm. High-quality visualization of major and distal arterial branches, including the Circle of Willis, was also achieved. Integrating manual perfusion and motorized pumping systems ensured vascular patency and realistic blood flow dynamics, making the models suitable for simulating real-life endovascular interventions. The study enhances the model’s capability to support complex procedures, emphasizing its practical application in advanced training. Conclusions: This study establishes that preparing FFCs is promising for developing versatile and optimized models for endovascular training. Sharing our preparation techniques will allow other institutions to replicate these models to enhance their training programs. Continued improvements could make FFC models essential tools for training the next generation of endovascular specialists. Prior models have been created, and our institutional experience highlights the foundation of these techniques, whereas future studies will aim to test these models in trainees.